The Impact of Broadband Diffusion in Assessing Innovation at the Institutions of Higher Learning in Kenya - Muchiri, Rajab Philip (Researchgate, 2017)
Objective: The aim of the research was to study the impact of broadband diffusion in assessing innovation in institutions of higher learning in Kenya. Background: The Government of Kenya realized the importance of broadband provision to stimulate economic development through innovation and established the Kenya Education Network Trust (KENET) - a national research and education network that promotes the use of broadband in teaching, learning and research in institutions of higher learning in Kenya. The aim of KENET was to interconnect all the universities in Kenya by setting up a cost effective and sustainable private network with high speed access to the global internet. Methodology: This study applied descriptive survey research design and a logistic regression model was used as an inferential analysis tool in the quantitative analysis. Inferential statistics used to analyse the model were; overall model evaluation, goodness-of-fit statistics, and statistical tests of individual predictors and validations of predicted probabilities. Results: Reliability measures were above the recommended level of 0.70 as an indicator for adequate internal consistency. Inferential statistics used to analyse the model showed that the model performed well and was appropriate for the study. Conclusion: Broadband diffusion in institutions of higher learning in Kenya is inhibited by poor infrastructural development attributed to high costs of connections and bandwidth acquisition and a high demand for broadband among the students and staff. Policies in broadband regulation from the national government and institutional governance are prudent in controlling and enabling access to this important resource for innovative purpose
Keywords: Broadband diffusion; Innovation; Education; Internet; Bandwidth; Regression Model